N-Oleoylglycine and N-Oleoylalanine Do Not Modify Tolerance to Nociception, Hyperthermia, and Suppression of Activity Produced by Morphine - Rock, Erin M.; Limebeer, Cheryl L.; Sullivan, Megan T.; DeVuono, Marieka V.; Lichtman, Aron H.; Di Marzo, Vincenzo; Mechoulam, Raphael; Parker, Linda A. (Frontiers in Synaptic Neuroscience, 2021)
The endogenous amide N-Oleoylglycine (OlGly) and its analog N-Oleoylalanine (OlAla), have been shown to interfere with the affective and somatic responses to acute naloxone-precipitated morphine withdrawal. Here we evaluated the potential of these endogenous fatty acid amides to modify tolerance to anti-nociception, hyperthermia, and suppression of activity produced by morphine in male Sprague-Dawley rats. Although rats did develop tolerance to the hypolocomotor and analgesic effects of morphine, they did not develop tolerance to the hyperthermic effects of this substance. Administration of neither OlGly nor OlAla interfered with the establishment of morphine tolerance, nor did they modify behavioral responses elicited by morphine on any trial. These results suggest that the effects of OlGly and OlAla on opiate dependence may be limited to naloxone-precipitated withdrawal effects.